2021
DOI: 10.3389/fpls.2021.651606
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Variations in the Photosynthetic Characteristics and the Gas Exchange Simulations of Two Rice Cultivars Grown at Ambient and Elevated CO2

Abstract: Investigating the diurnal and seasonal variations of plant photosynthetic performance under future atmospheric CO2 conditions is essential for understanding plant adaptation to global change and for estimating parameters of ecophysiological models. In this study, diurnal changes of net photosynthetic rate (Anet), stomatal conductance (gs), and photochemical efficiency of PSII (Fv′/Fm′) were measured in two rice cultivars grown in the open-top-chambers at ambient (∼450 μmol mol–1) and elevated (∼650 μmol mol–1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…Meanwhile, significant mean squares due to the interaction between genotypes and seasons were significant for all studied traits indicated that genotypes behaved differently in both summer growing seasons. These results are in line with those obtained by several investigators [6,8,9,10,11,24,25,26,27].…”
Section: C-photosynthetic Parameterssupporting
confidence: 93%
“…Meanwhile, significant mean squares due to the interaction between genotypes and seasons were significant for all studied traits indicated that genotypes behaved differently in both summer growing seasons. These results are in line with those obtained by several investigators [6,8,9,10,11,24,25,26,27].…”
Section: C-photosynthetic Parameterssupporting
confidence: 93%
“…Despite the consistent stomatal responsiveness in B. distachyon, we observed a significant influence of the time of the day on light-response stomatal kinetics. While diurnal variation on gas exchange has been well described for C 3 species (de Dios, 2017; Matthews et al, 2017;Miao et al, 2021;Roussel et al, 2009;Stangl et al, 2019;Vahisalu et al, 2008), the observed diurnal variation on stomatal responsiveness to changing light in the tightly regulated conditions of the IRGA chambers was compelling. Stomatal closure and opening speed were mainly affected by the time of the day and by steady-state g sw prior and/or after the change in light intensity.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the consistent stomatal responsiveness in B. distachyon , we observed a significant influence of the time of the day on light-response stomatal kinetics. While diurnal variation on gas exchange has been well described for C 3 species (Matthews et al, 2017; Miao et al, 2021; Resco de Dios, 2017; Roussel et al, 2009; Stangl et al, 2019; Vahisalu et al, 2008), the observed diurnal variation on stomatal responsiveness to changing light in the tightly regulated conditions of the IRGA chambers was compelling. Stomatal closure and opening speed were mainly affected by the time of the day and by steady-state g sw prior and/or after the change in light intensity.…”
Section: Discussionmentioning
confidence: 99%